Assessing the effects of allelopathic properties of organic mulches on liverwort control in container-grown ornamentals - Sidhu, Manjot Kaur; Chaudhari, Sushila; Lopez, Roberto; Patterson, Eric L.; Saha, Debalina (Frontiers in Agronomy, 2024)
Liverwort (Marchantia polymorpha) is a problematic weed in ornamental crop production. The major limitation of liverwort control is lack of herbicide options inside greenhouses and their potential to cause injury. The current research was undertaken to study the effectiveness of allelopathic properties of six different organic mulches including rice hull (RH), cocoa hull (CH), pine bark (PB), maple leaf (ML), shredded cypress (SC), and red hardwood (HW) for liverwort control. Mulch extracts were prepared and used to impregnate agar media at an increasing dose at 1X (2 mL mulch extract), 2X (4 mL), 3X (6 mL), and 4X (8 mL) rates, in a randomized complete block design. Ten liverwort gemmae were transferred to each petri dish and they were maintained inside a growth chamber. The number of gemmae germinating in each petri dish after 1 week and gemmae surviving at the end of 2 weeks was recorded. In greenhouse study, mulch extracts were applied to containers filled with substrate for assessing liverwort control. The mulch extracts or no extract (control) were applied to the containers uniformly at 1X (15 mL), 2X (30 mL), 3X (45 mL) or 4X (60 mL) rates, in a randomized complete block design. The percentage of substrate surface covered by liverwort thalli was visually estimated bi-weekly for 10 weeks. Fresh biomass of the thalli and gemmae cup counts in each pot were also recorded. After 1 week in the growth chamber, ML followed by SC, PB and RH extracts showed maximum suppression of liverwort gemmae germination. At 2 weeks, ML applied at either of the rates provided complete inhibition of liverwort growth. In greenhouse, all the mulch extracts were able to provide complete liverwort control for the first two weeks. All the mulches and rates of applications were significantly different from the control after 6, 8, and 10 weeks. PB and HW mulches showed excellent liverwort control and minimum fresh biomass of liverwort after 10 weeks as compared to other mulches. The allelopathic potential of the organic mulches can be a promising option for biopesticidal control of liverwort and a component of integrated liverwort management.